Temporary workers and firm performance: Empirical and systematic approaches from Eastern and Central European countries. Issue 5 (15th March 2020) - Moric, Ilija; Pekovic, Sanja; Perović, Đurđica; Roblek, Vasja; Pejic Bach, Mirjana
Abstract : Purpose: Although temporary work arrangements play a strategically important role in contemporary economic development, its influence on firm performance has remained elusive. In our work we measure firm performance from the systematic perspective, including both innovation and financial performance. Therefore, the purpose of this study is to test a model that specifies the influence of temporary work arrangements on the two indicators of firm performance, namely, innovation and sales. Design/methodology/approach: This research is based on the Business Environment and Enterprise Performance Survey (BEEPS, 2009 ) created by the European Bank for Reconstruction and Development and the World Bank. As the relationship between temporary workers and firm performance could be contingent on institutional setting, we divide our sample in three country groups: European Union (EU), European countries outside the European Union (non-EU) and the Commonwealth of Independent States (CIS) countries. Furthermore, we analyze the actual question on all three groups of countries separately. Findings: Findings provide support for the positive relationship between the percentage of temporary workers and innovation performance. On the other hand, the evidence reveals a negative link between the percentage of temporary workers and financial performance measured by sales. Taking into account country-specific effects, the results remain negative when examining the influence of the percentage of temporary workers on the financial performance measured by sales for all three country groups (EU, non-EU and CIS countries). However, the positive and significant effect of the share of temporary workers on innovation performance holds only for non-EU and CIS countries but is not observed for EU countries. Practical implications: Given the importance of temporary work arrangements in terms of a systematic approach in contemporary business, policymakers should continue to work on improving their status to overcome potential negative outcomes related to the temporary workers' engagement. In addition, managers of the firms should be aware that temporary workers could be a valuable source of innovation; however, they could hamper other aspects of firm performance. Therefore, they should be cautious when hiring temporary workers and find the "best balance" between permanent and temporary workers. Originality/value: The obtained findings highlight the importance of performance context systematic approach in studying the impact of temporary workers and firm performance. Based on the obtained findings, we may suggest that knowledge and creativity accumulation through temporary workers' engagement is beneficial for innovation performance improvement. Conversely, long-lasting labour engagement is necessary for financial performance improvement.